Melatonin decreases muscular oxidative stress and inflammation induced by strenuous exercise and stimulates growth factor synthesis. Issue 2 (28th January 2015) - Borges, Leandro da Silva; Dermargos, Alexandre; Junior, Edenilson Pinto da Silva; Weimann, Eleine; Lambertucci, Rafael Herling; Hatanaka, Elaine
Abstract Strenuous exercise is detrimental to athletes because of the overproduction of reactive oxygen species. Melatonin, a classic antioxidant, has been shown to exhibit beneficial effects regarding intense exercise and tissue repair. In this study, we evaluated the onset and resolution of inflammation in melatonin‐treated and nontreated rats subjected to a strenuous exercise session. We also analyzed the formation of thiobarbituric acid reactive substances (TBARS) and the activities of catalase (CAT), glutathione peroxidase (GPx), and superoxide dismutase (SOD). Control and treated rats were subjected to exhaustive exercise after a period of 10 days of melatonin treatment (20 mg/dL). Plasma and muscle levels of tumor necrosis factor‐alpha (TNF‐α), interleukin 1 beta (IL‐1β), interleukin 6 (IL‐6), cytokine‐induced neutrophil chemoattractant‐2‐alpha/beta (CINC‐2α/β), l‐selectin, macrophage inflammatory protein‐3‐alpha (MIP‐3α), and vascular endothelial growth factor (VEGF) were measured prior to, immediately after, and 2 hr after exercise. Our data revealed decreases in the muscle concentrations of IL‐1β (35%), TNF‐α (13%), IL‐6 (48%), and TBARS (40%) in the melatonin‐treated group compared with the control group. We also observed decreases in the plasma concentrations of IL‐1β (17%) in the melatonin‐treated group. VEGF‐α concentrations and SOD activity increased by 179% and 22%, respectively, in the melatonin‐treated group compared with the control group. We concluded that muscle inflammation and oxidative stress resulting from exhaustive exercise were less severe in the muscles of melatonin‐treated animals than in the muscles of control animals. Thus, melatonin treatment may reverse exercise‐induced skeletal muscle inflammation and stimulate growth factor synthesis.